Expression of CDX2 in normal and neoplastic human colon tissue and during differentiation of an in vitro model system - Qualtrough, D; Hinoi, T; Fearon, E; Paraskeva, C (Gut, 2002)
Background: The Cdx genes are expressed in the colorectal epithelium and are frequently downregulated during tumorigenesis. Overexpression of Cdx genes has been shown previously to result in cellular differentiation. Aim: To study expression of CDX2 in normal and neoplastic human colon using a newly isolated monoclonal antibody. To define expression of CDX1 and CDX2 in an in vitro model system of colorectal tumour progression and to ascertain whether these are subject to regulation during differentiation. Methods: Normal and neoplastic human colon was immunostained for CDX2. CDX1 and CDX2 expression was assayed in cell lines derived from premalignant colonic adenomas by western blotting. Differentiation was induced by sodium butyrate treatment or post confluent growth, and changes in CDX expression compared with carcinoma cell lines with low levels of CDX expression. Results: CDX2 protein displayed no gradient of expression within the colonic crypt. Cell lines derived from adenomas, with high levels of CDX1 and CDX2, showed no regulation of these proteins when induced to differentiate by butyrate or confluency. CDX expression in these cell lines was independent of their APC or Ras status. CDX1 and CDX2 were expressed at very low levels in some carcinoma cell lines and were modestly upregulated on differentiation but were not restored to levels seen in adenoma cells. Conclusion: The lack of significant regulation on cellular differentiation and the absence of a detectable gradient in the crypt implies that CDX2 may confer tissue specificity but may not play the previously suggested role in crypt patterning.